2018
DOI: 10.3150/16-bej896
|View full text |Cite
|
Sign up to set email alerts
|

Determinantal point process models on the sphere

Abstract: We consider determinantal point processes on the d-dimensional unit sphere S d . These are finite point processes exhibiting repulsiveness and with moment properties determined by a certain determinant whose entries are specified by a so-called kernel which we assume is a complex covariance function defined on S d × S d . We review the appealing properties of such processes, including their specific moment properties, density expressions and simulation procedures. Particularly, we characterize and construct is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 28 publications
0
46
0
Order By: Relevance
“…Point process techniques routinely deal with data observed in a restricted subset of the spatial domain. However, statistical techniques for point processes on the sphere (Ripley, ; Bahcall & Soneira, ; Scott & Tout, ; Raskin, ; Robeson et al, ; Møller et al, ) are still surprisingly underdeveloped. In principle, this is just a matter of adapting the existing methodology for point patterns in two‐dimensional space (Diggle, ; Møller & Waagepetersen, ; Baddeley et al, ) to the sphere.…”
Section: Introductionmentioning
confidence: 99%
“…Point process techniques routinely deal with data observed in a restricted subset of the spatial domain. However, statistical techniques for point processes on the sphere (Ripley, ; Bahcall & Soneira, ; Scott & Tout, ; Raskin, ; Robeson et al, ; Møller et al, ) are still surprisingly underdeveloped. In principle, this is just a matter of adapting the existing methodology for point patterns in two‐dimensional space (Diggle, ; Møller & Waagepetersen, ; Baddeley et al, ) to the sphere.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, properties of Legendre polynomials (see Szegö, ) imply that correlations based on geodesic distance can attain any value between −1 and +1. Another argument in favour of the great circle distance is that the differentiability of a given covariance function depending on the great circle distance can be modeled by imposing a given rate of decay of the associated 2‐Schoenberg coefficients false{bkfalse}k=0, as shown in Møller et al () or even by modeling the rate of decay of the associated 2‐Schoenberg functions in , as shown by Clarke et al ().…”
Section: Second‐order Approachesmentioning
confidence: 99%
“…Notable attempts have been made by Guinness and Fuentes (), with partial success. Møller et al () suggest modeling the n ‐Schoenberg coefficients (see Appendix A for details) while imposing a given rate of decay, but this does not allow for explicit closed forms. Compact Supports with Differentiable Temporal Margins. A potential drawback of the space–time construction as in Theorem is that it only allows for temporal margins that are non‐differentiable at the origin.…”
Section: Research Problemsmentioning
confidence: 99%
“…Some exceptions can be found in Møller et al (2015), where it is shown that the 1-Schoenberg coefficients associated to Wendland functions have oscillating behaviors. This makes extremely difficult to apply our results for our cases and opens future researches oriented to finding other criteria for equivalence of Gaussian measures over the sphere.…”
Section: Discussionmentioning
confidence: 99%
“…Let p i ∈ (0, 1) and τ i > 0, i = 1, 2 be the parameters of the negative Binomial distribution on S d (Møller et al, 2015), given by…”
Section: Multiquadric Covariance Functionmentioning
confidence: 99%